‘Painting with words’: Color terminology and pragmatic resonance in Alice Walker’s The Color Purple (1982) - Anwer, Rewaa (Research Journal in Advanced Humanities, 2023)
This study delves into an analysis of how Alice Walker strategically uses color descriptions in her work ‘The Color Purple’ to intricately depict life in the rural South during the early 1900s. In literature, colors often serve as conveyors of emotion and meaning, and in this case, Walker adeptly employs them to symbolize pivotal themes encompassing race, gender empowerment, and spirituality. The researcher enriches the portrayal of characters, setting, and the overall narrative by employing a diverse spectrum of color terminologies, effectively endowing colors with character-like qualities. Beyond a mere chromatic shade, the title ‘The Color Purple’ embodies a realm saturated with the significance of color. Walker’s masterful handling of color descriptions crafts a multi-dimensional and evocative representation of the experiences of southern Black women during that epoch. The linguistic apparatus of color terminology imparts a poetic avenue for articulating concealed or unspoken facets of their lives, ultimately thrusting them into the spotlight.